Sustainable Business Solutions For Traditional Handicraft Product In The Northwestern Provinces Of Vietnam - Hai Nguyen Thanh; Duong Nguyen Thuy; Huy Dinh Tran Ngoc; Hien Dinh Thi (Management)
Local tourism development requires us to consider many solutions, among them is sustainable solutions for business development of traditional handicraft products. This study is done based on surveys of northwestern provinces of Vietnam, in which authors use statistics, questionnaires and charts.